A ‘compare and contrast’ exercise: wrapping versus personalised external aortic root support (PEARS) - Treasure, Tom (J Cardiothorac Surg, 2016)
Wrapping of the aorta and personalised external aortic root support (PEARS) both have the purpose of preventing further expansion of the ascending aorta in order to reduce the risk of aortic dissection and to spare the patient the disastrous consequences of aortic rupture. For the first time, Plonek and colleagues have reported systematically the CT appearances of a series of cases of wrapping. They illustrate the important finding that there are residual spaces between the aorta and the wrap. PEARS by contrast is intimately in contact with the aorta due to its personalised design and is fully incorporated due it construction from a porous mesh. A limitation of PEARS is that it is, of its nature, a planned and elective operation while wrapping can be undertaken during an emergency operation and can be used without prior planning as an intraoperative decision.